Seven‐Year Outcomes of the Silicone Arthroplasty in Rheumatoid Arthritis Prospective Cohort Study. Issue 7 (9th June 2017) - Chung, Kevin C.; Kotsis, Sandra V.; Burns, Patricia B.; Burke, Frank D.; Wilgis, E. F. Shaw; Fox, David A.; Kim, H. Myra
Abstract : Objective: Rheumatoid arthritis (RA) causes destruction of the metacarpophalangeal (MCP) joints, leading to hand deformities, pain, and loss of function. This study prospectively assessed long‐term functional and health‐related quality‐of‐life outcomes in RA patients with severe deformity at the MCP joints. Methods: RA patients between ages 18 to 80 years with severe deformity at the MCP joints were referred to 1 of the 3 study sites. Subjects who elected to undergo silicone metacarpophalangeal joint arthroplasty (SMPA) while continuing with medical management were followed in the SMPA cohort. Subjects who elected to continue with medical management alone without surgery were followed in the non‐SMPA cohort. Objective measurements included grip and pinch strength as well as arc of motion, ulnar drift, and extensor lag of the MCP joints. Patient‐reported outcomes included the Michigan Hand Questionnaire (MHQ) and the Arthritis Impact Measurement Scales questionnaire. Radiographs of SMPA implants were assessed and graded as intact, deformed, or fractured. Results: MHQ scores showed large improvements post‐SMPA, and baseline‐adjusted expected outcomes in the SMPA group were significantly better at year 7 in function, aesthetics, satisfaction, and overall score compared to non‐SMPA. SMPA subjects did not improve in grip or pinch strength, but achieved significant improvement and maintained the improvement long term in ulnar drift and extensor lag. Conclusion: Benefits of the SMPA procedure are maintained over 7 years with low rates of implant fracture or deformity. Non‐SMPA patients remained stable in their hand function over the 7‐year study duration.